Geriatrische Intensivpatienten: Perspektiven und Grenzen der geriatrischen Intensivmedizin - Müller-Werdan, U.; Michels, G.; Heppner, Hans Jürgen (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2018)
Critically ill geriatric patients are vitally endangered due to the aging processes of organs, the frequently existing multimorbidity with subsequent polypharmacy and the typical geriatric syndrome of functional impairments. Aging processes in organs lower the clinical threshold for organ dysfunction and organ failure. Physiological organ aging processes with practical consequences for intensive care medicine are atypical manifestion of sepsis in immunosenescence, altered pharmacokinetics, reduced tolerance to hypovolemia due to proportionally reduced water compartment of the body in old age, the frequently only apparently normal function of the kidneys and the continuous reduction in pulmonary function in old age. The main reasons for changes in therapeutic targets are the will of the patient and risk-benefit considerations. The guidelines of the ethics section of the German Interdisciplinary Association for Intensive Care and Emergency Medicine (DIVI) provide assistance and suggestions for a structured decision-making process.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Aging; Biomarkers; End of life care; Frailty; Intensive care